Development Of A Diagnostic Instrument Based On Teaching At The Right Level For Assessing Elementary School Students' Reading Ability - sintayana; Baiq Desi milandari; Siti Johar Manikam; Bunga Oriza Satifa; Wina Fadila Aulia; St. Hajar (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This study aims to develop a diagnostic instrument for reading ability based on Teaching at the Right Level (TaRL) to map the reading abilities of primary school pupils according to their proficiency levels. The development of this instrument was prompted by the limitations of existing reading assessments, which remain general in nature and are therefore unable to identify variations in pupils’ reading abilities as a basis for designing differentiated learning. This study employed the Research and Development (R&D) method, adapting the Borg and Gall model up to the limited pilot test stage, which involved 38 pupils in Years 1 and 2 of primary school. Research data were obtained through validation by linguists, TaRL assessment experts and education practitioners, pupil response questionnaires, and the results of reading ability mapping, and were subsequently analysed using descriptive statistics. The novelty of this research lies in the development of a diagnostic instrument designed based on reading ability levels within the TaRL approach, which has undergone a process of validation and practical testing prior to implementation. The research findings indicate that the instrument meets the validity criteria, is highly practical, and is capable of systematically mapping pupils’ reading abilities from beginner level to paragraph level. These findings suggest that the instrument developed is suitable for use as a diagnostic assessment tool to support the identification of reading abilities and to form the basis for the design of differentiated learning tailored to the learning needs of primary school pupils.